Molecular genetic background of an autosomal dominant hypercholesterolemia in the Czech Republic - Tichý, Lukáš; Fajkusová, Lenka; Zapletalová, Petra; Schwarzová, Lucie; Vrablík, Michal; Freiberger, Tomáš (Physiological research, 2017)
Autosomal dominant hypercholesterolemia (ADH), more known as familial hypercholesterolemia (FH), is a lipid metabolism disorder characterized by an elevation in low-density lipoprotein cholesterol (LDL-C) and increased risk for cardiovascular disease. In this study, we assessed a spectrum of mutations causing ADH in 3914 unrelated Czech patients with clinical diagnosis of hypercholesterolemia. Samples have been collected within the framework of the MedPed project running in the Czech Republic since 1998. So far we have found 432 patients (11.0 %) with the APOB gene mutation p.(Arg3527Gln) and 864 patients (22.1 %) with the LDLR gene mutation. In 864 probands carrying the LDLR gene mutation, 182 unique allelic variants were detected. We have identified 14 patients homozygous for mutations in the LDLR or APOB genes. We performed function analyses of p.(Leu15Pro) and p.(Gly20Arg) sequence variations.
Keywords: Genetic Background; Receptors, LDL; Cholesterol, LDL; apolipoprotein B-100; LDL-cholesterol; LDL-receptory; lidé; Hyperlipoproteinemia Type II; genetická variace; Czech Republic; Humans; Genetic Variation; hyperlipoproteinemie typ II; genetické pozadí; Česká republika; Apolipoprotein B-100